2014
DOI: 10.3892/mmr.2014.2482
|View full text |Cite
|
Sign up to set email alerts
|

MacroH2A suppresses the proliferation of the B16 melanoma cell line

Abstract: Abstract. MacroH2A is the most frequently altered histone, which participates in cancer progression. Increasing evidence demonstrates that cancer progression could be regulated by macroH2A by affecting the cell cycle. In the present study, it was demonstrated that macroH2A suppresses melanoma cell progression and the molecular mechanisms underlying this process were examined. The interference and overexpression vectors of macroH2A were constructed and then transferred into B16 melanoma cells and, following tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…MacroH2A has emerged as a critical epigenetic regulator of cancer, and aberrant expression of macroH2A has been observed in many cancer types including CRC (Cantarino et al, 2013). Recently, macroH2A was also shown to repress transcription of CDK4 and CCND1 , as well as CDK8 (Lei et al, 2014, Yang et al, 2015). We speculate that the interaction of H19 with macroH2A protein could sequester the suppressive effect of macroH2A on transcription of above genes, and might represent the initial mechanism of H19 function.…”
Section: Discussionmentioning
confidence: 99%
“…MacroH2A has emerged as a critical epigenetic regulator of cancer, and aberrant expression of macroH2A has been observed in many cancer types including CRC (Cantarino et al, 2013). Recently, macroH2A was also shown to repress transcription of CDK4 and CCND1 , as well as CDK8 (Lei et al, 2014, Yang et al, 2015). We speculate that the interaction of H19 with macroH2A protein could sequester the suppressive effect of macroH2A on transcription of above genes, and might represent the initial mechanism of H19 function.…”
Section: Discussionmentioning
confidence: 99%
“…Lei et al [7] showed that high expression of mH2A suppressed melanoma cell progression and arrested cells in the G2/M phase. Thus, we hypothesized that an alteration in mH2A expression could contribute to a change in the phenotype of UMs, promoting tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the loss of mH2A isoforms in cutaneous melanomas is correlated with increasing malignant phenotypes: this mechanism would seem to be mediated by the upregulation of CDK8, which inhibits the proliferation of melanoma cells. During CM progression, tumor cells show a low expression of mH2A, and conversely, high levels of mH2A expression correlate with a better prognosis [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the effect of macroH2A on melanoma cell progression in culture was also linked to cell cycle‐related genes. Overexpression of macroH2A suppressed melanoma cell progression and arrested the cells in G2/M stage through inhibition of cyclin D1, cyclin D2, and CDK6 and CDK8 expression (Lei et al., ).…”
Section: Histone Variants and Melanomamentioning
confidence: 99%